The pulsation modes of the pre-white dwarf PG 1159-035 - Althaus, Leandro Gabriel (2008)
Context. PG 1159-035, a pre-white dwarf with Teff ≃ 140000 K, is the prototype of both two classes: the PG 1159 spectroscopic class and the DOV pulsating class. Previous studies of PG 1159-035 photometric data obtained with the Whole Earth Telescope (WET) showed a rich frequency spectrum allowing the identification of 122 pulsation modes. Analyzing the periods of pulsation, it is possible to measure the stellar mass, the rotational period and the inclination of the rotation axis, to estimate an upper limit for the magnetic field, and even to obtain information about the inner stratification of the star. Aims. We have three principal aims: to increase the number of detected and identified pulsation modes in PG 1159-035, study trapping of the star's pulsation modes, and to improve or constrain the determination of stellar parameters. Methods. We used all available WET photometric data from 1983, 1985, 1989. 1993 and 2002 to identify the pulsation periods. Results. We identified 76 additional pulsation modes, increasing to 198 the number of known pulsation modes in PG 1159-035, the largest number of modes detected in any star besides the Sun. From the period spacing we estimated a mass M/M⊙= 0.59 ±0.02 for PG 1159-035, with the uncertainty dominated by the models, not the observation. Deviations in the regular period spacing suggest that some of the pulsation modes are trapped, even though the star is a pre-white dwarf and the gravitational settling is ongoing. The position of the transition zone that causes the mode trapping was calculated at rc/R* = 0.83 ± 0.05. From the multiplet splitting, we calculated the rotational period Prot = 1.3920 ± 0.0008 days and an upper limit for the magnetic field, B < 2000 G. The total power of the pulsation modes at the stellar surface changed less than 30% for ℓ = 1 modes and less than 50% for ℓ = 2 modes. We find no evidence of linear combinations between the 198 pulsation mode frequencies. PG 1159-035 models have not significative convection zones, supporting the hypothesis that nonlinearity arises in the convection zones in cooler pulsating white dwarf stars.